Strategi Peningkatan Penerimaan Dana Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kepahiang - Zarkasih, Tria; Pakkana, Mukhaer (Jurnal Ilmiah Ekonomi Islam, 2023)
The low level of zakat receipt at Baznas Kepahiang which has a majority Muslim community raises important problems to be addressed immediately. This research was conducted to help discover the right strategy to increase zakat acceptance. Using grounded theory research methods, the author formulates relevant theories based on field facts. The results revealed that the main obstacle causing the low receipt of zakat funds at Baznas Kepahiang was influenced by the target that was not achieved due to minimal knowledge about zakat and Baznas. The strategy to increase the receipt of zakat funds at Baznas Kepahiang is formulated in the form of socialization and education, transparency and accountability, partnerships, and optimization of the use of digital technology where socialization and education require transparency and accountability in campaign materials to introduce Baznas Kepahiang and its activities. Good and routine socialization and education will build partnership relationships. Socialization and education will run successfully if supported by the use of digital technology. Transparency and accountability that are done well will maintain partner trust. Transparency and accountability require the growing use of digital technologies. Partnership relationships will be closer if strengthened by the use of digital technology.